The Use of Duren Seed Flour in the Making of Pancakes - Nisa Rahmaniyah Utami; Muhamad Fachry Irvani (Media Pendidikan Gizi dan Kuliner, 2021)
Pancake is a dish that has a sweet and savory taste from butter dough baked in a frying pan and is round and flat. Wheat flour is one of the basic ingredients in making pancakes so as to reduce dependence on wheat flour, namely by optimizing local ingredients that are still lacking in utilization, namely durian seeds and durian seeds. to be used as flour in the manufacture of a food. therefore the author replaces wheat flour with durian seed flour in making pancakes. This study uses a questionnaire method with a preference test from the panelists, many samples studied amounted to 3 expert panelists, 30 consumer panelists. The author is looking for a good formulation to be applied to pancake products before being distributed to the panelists. The author finds out the results of the study by looking for the mean, median, mode, and standard deviation data. The results obtained by taking the average value of 4 (four) aspects, namely color, aroma, texture, and taste. The results of this study indicate that the use of durian seed flour in making pancakes can be said to be successful with the results of the preference test which are dominated by liking.